2014
DOI: 10.3892/mmr.2014.1984
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13 stimulates angiogenesis by promoting cross-talk between AMP-activated protein kinase and Akt signaling in myocardial microvascular endothelial cells

Abstract: Abstract. Currently, there is major interest in the functions of apelin-13, an endogenous ligand for the orphan G-protein coupled receptor APJ, a receptor that closely resembles the angiotensin receptor AT1. In the present study, the role of apelin-13 in angiogenesis and its mechanism as a novel angiogenic factor in myocardial microvascular endothelial cells (MMVECs) was investigated. It was revealed that apelin-13 can promote proliferation, migration and tube formation in MMVECs. In addition, apelin-13 dose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…In agreement, chronic administration of the native apelin peptide reduced RVSP in mouse and rat models of PAH (Alastalo et al, 2011;Falcão-Pires et al, 2009). AMPK mediated the pro-angiogenic effects of apelin and activation of AMPK has beneficial effects in PAH animal models (Chandra et al, 2011;Yang et al, 2014). Taken (Yang, Read, et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In agreement, chronic administration of the native apelin peptide reduced RVSP in mouse and rat models of PAH (Alastalo et al, 2011;Falcão-Pires et al, 2009). AMPK mediated the pro-angiogenic effects of apelin and activation of AMPK has beneficial effects in PAH animal models (Chandra et al, 2011;Yang et al, 2014). Taken (Yang, Read, et al, 2017).…”
Section: Discussionmentioning
confidence: 67%
“…Importantly, eNOS functions beyond generating a vasodilator, as eNOS gene transfer restored the microvascular loss in the MCT model (Zhao et al, 2006). AMPK mediated the pro-angiogenic effects of apelin and activation of AMPK has beneficial effects in PAH animal models (Chandra et al, 2011;Yang et al, 2014). We have found that MM07 could increase the phosphorylation of AMPKa in endothelial cells.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition, apelin promotes angiogenesis by activating AMPK activation in myocardial microvascular endothelial cells (Yang et al . ) and apelin is known to stimulate vasculogenesis in the placenta (Kurowska et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering these findings, the present study used late EPCs to assess angiogenesis under treatment with Tβ4. It was demonstrated that the Akt/eNOS pathway is a critical component in regulating the signaling of multiple biological processes (22,23). Through the activation of this pathway, the migration and anti-apoptotic ability of late EPCs increased, and finally promoted angiogenesis to aid ischemic myocardial survival.…”
Section: Discussionmentioning
confidence: 99%